The Demand for, and Impact of, Youth Internships: Evidence from a Randomized Experiment in Yemen - David McKenzie; Nabila Assaf; Ana Paula Cusolito (Institute for the Study of Labor (IZA), 2015)
This paper evaluates a youth internship program in the Republic of Yemen that provided firms with a 50 percent subsidy to hire recent graduates of universities and vocational schools. The first round of the program took place in 2014 and required both firms and youth to apply for the program. The paper examines the demand for such a program, and finds that in the context of an economy facing substantial political and economic uncertainty, it appears there is an oversupply of graduates in science, technology, engineering, and mathematics, and a relative undersupply of graduates in marketing and business. Conditional on the types of graduates firms were looking to hire as interns, applicants were then randomly chosen for the program. Receiving an internship resulted in an almost doubling of work experience in 2014, and a 73 percent increase in income during this period compared with the control group. A short-term follow-up survey conducted just as civil conflict was breaking out shows that internship recipients had better employment outcomes than the control group in the first five months after the program ended.
Keywords: O12; O15; J08; J16; 330; internship; active-labor market program; randomized experiment; fragile state